Mastering macOS programming : combine macOS programming with Cocoa and Swift 3 to build powerful applications - Grimshaw, Stuart (Packt Publishing, 2017)
Take your macOS Sierra to the next level using the latest tools, designs, and best coding practices while developing with Swift 3.0 About This Book Learn to harness the power of macOS with the elegance of the Swift programming language Become highly competent in building apps on the macOS platform Get the most in-depth guide with a hands-on approach on the latest version of macOS Who This Book Is For This book is for developers who have some experience with macOS and want to take their skills to next level by unlocking the full potential of latest version of macOS with Swift 3 to build impressive applications. Basic knowledge of Swift will be beneficial but is not required. What You Will Learn Combine beautiful design with robust code for the very best user experience Bring the best coding practices to the new macOS Sierra See what's new in Swift 3.0 and how best to leverage the Swift language Master Apple's tools, including Xcode, Interface Builder, and Instruments Use Unix and other common command-line tools to increase productivity Explore the essential Cocoa frameworks, including networking, animation, audio, and video In Detail macOS continues to lead the way in desktop operating systems, with its tight integration across the Apple ecosystem of platforms and devices. With this book, you will get an in-depth knowledge of working on macOS, enabling you to unleash the full potential of the latest version using Swift 3 to build applications. This book will help you broaden your horizons by taking your programming skills to next level. The initial chapters will show you all about the environment that surrounds a developer at the start of a project. It introduces you to the new features that Swift 3 and Xcode 8 offers and also covers the common design patterns that you need to know for planning anything more than trivial projects. You will then learn the advanced Swift programming concepts, including memory management, generics, protocol orientated and functional programming and with this knowledge you will be able to tackle the next several chapters that deal with Apple's own Cocoa frameworks. It also covers AppKit, Foundation, and Core Data in detail which is a part of the Cocoa umbrella framework. The rest of the book will cover the challenges posed by asynchronous programming, error handling, debugging, and many other areas that are an indispensable part of producing software in a professional environment. By the end of this book, you will be well acquainted with Swift, Cocoa, and AppKit, as well as a plethora of other essential tools, and you will be ready to tackle much more complex and advanced software projects. Style and approach This comprehensive guide takes a hands-on practical approach incorporating a visually-rich format rather than a text heavy format. The focus is on teaching the core concepts through a series of small projects and standalone examples so you gain expertise with various aspects of macOS application development.